Nos trilhos da cidade : aspectos históricos dos transportes colectivos no Porto - Alves, Jorge Fernandes (2014)
In this article, we analyse the major policies regarding public transportation in the city of Oporto. We draw attention to its importance and to the history of some relevant events that marked the organization of transportation companies, the different types of transport and their relationship with users and local authorities.